Eritrea Education Sector Plan 2018-2022 - Ministry of Education of Eritrea (Global Partnership for Education, 2028)
The mission of the Ministry of Education of Eritrea during implementation of the new Education Sector Plan 2018-2022 is "to provide a quality and relevant education consistent with the national aspirations to all Eritrean."
KerkoCite.ItemAlsoKnownAs: 2339240:SIJKUS9W 2405685:ARMMKQ3F